Digital literacy in learning listening skill between English and Non-English Department students through educational video - Pudjiati, Danti; Fitria, Tira Nur (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2022)
As the usage of ICT in teaching and learning, digital literacy becomes well-liked for Indonesian English department and non-English department students from Jakarta and Central Java. This research is to investigate both the students’ listening comprehension and their insight into educational videos for improving their listening skills. The objectives are: 1) finding out the students listening comprehension through watching VOA Learning English, 2) obtaining the students' perception of listening to English?, 3) exploring students' preferences to listen through video?, 4) investigating the listening media and topic the students like to listen to?, 5) probing the students' familiarity with VOA Learning English? This research was a comparative study including descriptive statistics. The questionnaire results revealed that the students from the two campuses shared similarities and differences in their preferences to increase their listening skills through video. The students of the English department and non-English department listening comprehension were categorized as fair since most of them reached scores between seventy and eighty. The majority of both English department and non-English department students like to listening English. However, they prefer watching a video in the form of a combination between monolog and dialog. They were enjoy the song for improving their listening skill. They also commit that the VOA video was interesting since it was designed to help them in developing their English skills daily. Likewise, such videos performed native speakers as role models which are favored by English department and non-English department students. Besides, they like to receive the questions after the video ends.